2004
DOI: 10.1097/01.wcb.0000125648.03213.1d
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Indomethacin on Intracranial Pressure, Cerebral Perfusion and Extracellular Lactate and Glutamate Concentrations in Patients with Fulminant Hepatic Failure

Abstract: Summary: Uncontrolled increase in intracranial pressure (ICP) continues to be one of the most significant causes of early death in patients with acute liver failure (ALF). In this study, we aimed to determine the effects of indomethacin on ICP and cerebral perfusion pressure in twelve patients with ALF and brain edema (9 females/3 males, median age 49,5 (range 21 to 64) yrs.). Also changes in cerebral perfusion determined by transcranial Doppler technique (Vmean) and jugular bulb oxygen saturation (SvjO2) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(49 citation statements)
references
References 32 publications
0
48
0
1
Order By: Relevance
“…102 Chung and colleagues also demonstrated that indomethacin can prevent the development of ammonia-induced brain edema in rats that have undergone portocaval anastamosis. 103 In a chronic portocaval-shunted rat model, Cauli and colleagues showed that the NSAID ibuprofen restored the ability of the rats to learn the Y-task maze, in addition to normalization of the function of the glutamate-nitric oxide cyclic guanosine monophosphate enzyme pathway in the cerebral cortex.…”
Section: Non-steroidal Anti-inflammatoriesmentioning
confidence: 98%
“…102 Chung and colleagues also demonstrated that indomethacin can prevent the development of ammonia-induced brain edema in rats that have undergone portocaval anastamosis. 103 In a chronic portocaval-shunted rat model, Cauli and colleagues showed that the NSAID ibuprofen restored the ability of the rats to learn the Y-task maze, in addition to normalization of the function of the glutamate-nitric oxide cyclic guanosine monophosphate enzyme pathway in the cerebral cortex.…”
Section: Non-steroidal Anti-inflammatoriesmentioning
confidence: 98%
“…In our data, however, the position of the γ-CH 2 Glx at 2.34 ppm in all ALF patients and controls indicates that the main component of the Glx peaks in the white and grey matter brain tissue of ALF patients and controls is glutamate. Considering that sharply elevated extracellular brain glutamate concentrations have [22], the possibility of part of the Glx signal representing extracellular rather than intracellular glutamate should be considered. We conclude that of the total of up to 6 mmol/l Glx observed in the brains of ALF patients (Table 2), up to 5% might have been extracellular glutamate.…”
Section: Glutamate/glutamine (Glx)mentioning
confidence: 99%
“…Hyperventilation results in precapillary vasoconstriction (37) and while not recommended as a prophylactic measure, it is especially useful to control surges of ICP, a "pressure wave" that requires immediate medical therapy. A similar use can be assigned to indomethacin, a cerebral vasoconstrictor (38); the effects of the drug on the gastric mucosa and renal circulation preclude a prophylactic role.…”
Section: C) Therapeutic Optionsmentioning
confidence: 99%